MODELLING OF ELECTRICAL ENERGY CONSUMPTION OF ELECTRICAL DRIVES IN THROTTLE AND FREQUENCY REGIMES OF CONTROL - R. K. Gumerova; V. A. Chernyakhovskiy (Известия высших учебных заведений: Проблемы энергетики, 2017)
The relevance of this work is in development of mathematical model, which shows the advantage of frequency control of engines of pumps over throttle control. The object of study is boiler station of manufacturing plant. The aim of research is to compare two modes of engines of pumps: throttle control and frequency control, evaluation of energy-saving potential and calculation payback period of frequency controllers. The model was developed in MATLAB Simulink medium. The model was created on the basis of boiler station data. The boiler room includes nine types of pumps. These engines of pumps differ from each other in the manner of work. The monthly average outside temperature is an input parameter of a mathematical model. Temperature of water in supply line and value of pressure vary depending on the outside temperature. Working characteristics of pumps and engines are set with polynomials for throttle and frequency regimes of control. Logic blocks were created to regulate work of pumps depending on monthly average outside temperature. Modeling is prediction of electrical consumption by electrical consumers of boiler station. Time of modelling is 5 year. The modelling process is based on monthly average outside temperature during 5 past years Averaging of experiments results showed energy-saving potential 11% and effective values of payback times for all frequency controllers.